The effect of layer thickness ratio on the drug release behavior of alternating layered composite prepared by layer-multiplying co-extrusion - Zheng, Huiyu; Zhang, Cong; Liu, Guiting; Chen, Rong; Guo, Shaoyun (Frontiers in Bioengineering and Biotechnology, 2023)
Multi-layered drug delivery (MLDD) system has promising potential to achieve controlled release. However, existing technologies face difficulties in regulating the number of layers and layer-thickness ratio. In our previous works, layer-multiplying co-extrusion (LMCE) technology was applied to regulate the number of layers. Herein, we utilized LMCE technology to modulate the layer-thickness ratio to expand the application of LMCE technology. Four-layered poly(ε-caprolactone)-metoprolol tartrate/poly(ε-caprolactone)-polyethylene oxide (PCL-MPT/PEO) composites were continuously prepared by LMCE technology, and the layer-thickness ratios for PCL-PEO layer and PCL-MPT layer were set to be 1:1, 2:1 and 3:1 just by controlling the screw conveying speed. The in vitro release test indicated that the rate of MPT release increased with decreasing the thickness of the PCL-MPT layer. Additionally, when PCL-MPT/PEO composite was sealed by epoxy resin to eliminate the edge effect, sustained release of MPT was achieved. The compression test confirmed the potential of PCL-MPT/PEO composites as bone scaffolds.